Prenatal Yoga terhadap Penurunan Nyeri Lumbal 4-5 - Susanti, Mayra Rizky; Sulastri, Sulastri (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of prenatal yoga in reducing 4-5 lumbar pain in third trimester pregnant women. The method used was quasi experimental with a two-group pre-test and post-test design approach . The results showed that the p value in the Wilcoxon test results showed a significant difference in the level of lumbar pain 4-5 pre-test and post-test carried out in the experimental group, p=0.000 (p<0.05). The results of statistical processing carried out using the Mann Whitney test, the p value shows that there is a significant difference in lumbar pain 4-5 pre-test and post-test in the experimental group, namely p=0.004 (p<0.05). Conclusion, prenatal yoga is effective for decrease in lumbar pain 4-5 in third trimester pregnant women. Keywords: Prenatal Yoga, Lumbar Pain 4-5